1996
DOI: 10.1006/viro.1996.0030
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Mutant Bacteriophage T7 Deleted in Nonessential Genetic Elements, Gene19.5andm

Abstract: Half of the 55 potential genes of bacteriophage T7 appear to be dispensable. One of the major obstacles in the study of these nonessential genes is the difficulty in obtaining mutants. During a study of genes involved in the packaging of bacteriophage T7, we hypothesized that some nonessential genes may be required for optimal growth. Mutant phages lacking such nonessential genes may form plaques but grow slowly. One gene located at the extreme right end of the linear T7 genome, gene 19.5 with no known mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, a potential role in lysis is not entirely unexpected. A phage with a deletion of gene 19.5 (along with the adjacent M-hairpin) lyses late and mutant phages make small plaques ( Kim and Chung 1996 ), although much of this effect may be caused by the deletion of the hairpin ( Kim et al 1997 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a potential role in lysis is not entirely unexpected. A phage with a deletion of gene 19.5 (along with the adjacent M-hairpin) lyses late and mutant phages make small plaques ( Kim and Chung 1996 ), although much of this effect may be caused by the deletion of the hairpin ( Kim et al 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is no function assigned to this gene, but it is predicted to encode a short, membrane-spanning protein (by TMHMM; Krogh et al 2001 ; data not shown). A deletion mutant lacking gene 19.5 lyses late ( Kim and Chung 1996 ), although the observed effect on lysis can perhaps be largely explained by the deletion also removing a nearby hairpin. However, Kim et al (1997) have suggested that gene 19.5 acts to generate the hairpin, and if the hairpin triggers holin activity, 19.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that up to 50% of the genes of extensively studied bacteriophages such as T7 are non‐essential for plaque formation. These genes, although dispensable for phage growth under laboratory conditions, bear meaningful functions and some of them are known to interact with and inhibit host proteins (Kim and Chung, 1996).…”
Section: Discussionmentioning
confidence: 99%